Identifikasi senyawa fitokimia pada tepung terung pokak (Solanum torvum) terhadap 3 jenis metode pengeringan - Nunuk Helilusiatiningsih (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Pokak eggplant was quite popular abroad and in Indonesia spread over fertile land but still limited for public consumption. Pokak eggplant potential contains phytochemicals and functions as a herbal medicine for health. This research aimed to analyze the phytochemical compounds in dried pokak eggplant using tree types drying methods into flour. There were types of drying methods using sunlight, vacuum dryer and try dryer. The parameters observed were DPPH, total phenol, tannins, flavonoids, proximate test, vitamin C. The results showed the phytochemical components: a) pokak flour (sunlight method) Contains DPPH 88.10%, total phenol 37.32 mg/g, tannins 1.03 mg/g, flavonoids 5.11 mg/g, water content 6.92%, ash content 3.66%, protein 11, 51%, 5.38% fat, 72.53% carbohydrates, 0.21% vitamin C; b) pokak flour (vacuum dryer method) has DPPH of 92.81%, total phenol 77.35 mg/g, tannins 1.24 mg/g, flavonoids 2.75 mg/g, moisture content of 7.62%, ash content of 2, 82%, 22.66% protein, 3.25% fat, 65.51% carbohydrates, 2.44% vitamin C; c) pokak flour (try dryer method) had DPPH 85.15%, total phenol 22.91 mg/g, tannins 0.63 mg/g, flavonoids 2.43 mg/g, water content 6.89%, ash content 3.29%, 21.28% protein, 7.04% fat, 61.5% carbohydrates, 0.39% vitamin C. The drying method can be used as a recommendation for the identification of phytochemical compounds.